A Comparative Study of Shear-Wave Elastography and Strain Elastography on a Breast Phantom for Diagnosis of Tumor and Cyst - Al-Qahtani, Mahdi; Mirza, Eraj Humayun; Al-Qahtani, Mubarak Dhafer; Al-Muqati, Mohammed Fahad (British Journal of Healthcare and Medical Research, 2015)
A lump in breast may suggest a possible development of breast cancer. As the tumor develops, it changes the physical property of the tissue by changing its stiffness. To detect the tumor generally mammography is performed. The findings of mammography are often inaccurate as it does not take into account the stiffness of tissue. Elastography is an imaging technique to measure the stiffness of tissues. In the current study, we have used a breast phantom to analyze differences between a tumor and a cyst via comparing shear-wave elastography and strain elastography techniques. Both the techniques performed equally for the diagnosis of tumour. However, it is suggested that strain elastography must be used in the diagnosis of a cyst as it provides enhanced details of the surrounding tissues.